Parenting styles, empathy and aggressive behavior in preschool children: an examination of mediating mechanisms - Lin, Zhumei; Zhou, Ziqian; Zhu, Lijun; Wu, Weige (Frontiers in Psychology, 2023)
Introduction This study examined the interplay between parenting styles, empathy, and aggressive behavior in Chinese preschool children aged 3–5 years. Methods Data were collected from 87 participants using the Child Behavior Checklist, Children’s Empathy Quotient, and Parenting Style Questionnaire, and were subsequently analyzed. Results The findings revealed significant age and gender differences in empathy, but not in parenting styles or aggressive behavior. Additionally, a substantial correlation was identified between authoritarian parenting style and aggressive behavior, as well as between children’s empathy levels and aggressive behavior. This indicates that empathy may act as a mediator between parenting style and aggressive behavior. Discussion Our findings suggest that an authoritarian parenting style influences aggressive behavior both directly and indirectly through its effect on children’s empathy. These results point toward the possibility that an authoritarian parenting style may stifle the development of empathy in preschool children, subsequently heightening their aggressive behavior.